1994
DOI: 10.5271/sjweh.1396
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases among foundry workers exposed to carbon monoxide.

Abstract: 1KOSKELA R-S. Cardiovascular diseases among foundry workers exposed to carbon monoxide. Scand J Work Environ Health 1994;20:286-93. OBJECTIVES -The study investigated long-term effects of carbon monoxide (CO) exposure on foundry workers' morbidity and mortality from cardiovascular diseases. METHODS -The study population comprised a cohort of 2857 men hired in 1950-1972 by 20 Finnish foundries and also 931 men who were still active in 1972, exposed for at least 4.2 years, took part in a health examination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…A Finnish study (202) observed an increased mortality from IHD among foundry workers. The long-term effects of carbon monoxide may aggravate arteriosclerotic disease (203).…”
Section: Circulatory Diseasesmentioning
confidence: 99%
“…A Finnish study (202) observed an increased mortality from IHD among foundry workers. The long-term effects of carbon monoxide may aggravate arteriosclerotic disease (203).…”
Section: Circulatory Diseasesmentioning
confidence: 99%
“…In addition, Mb facilitated diffusion probably contributes to tissue oxygenation over a range of O 2 metabolic demand, 5,86 but this effect has not been implemented in the model. The model prediction of lower myocardial blood and tissue O 2 tensions during exercise in the presence of CO supports the observations of increased risk of cardiac injury in a working population exposed to CO. 50,53,77 Concerns and Limitations…”
Section: Effects Of Co Exposure During Exercisementioning
confidence: 97%
“…36,62,87 There is also evidence that workers who are chronically exposed to CO have an increased risk for cardiovascular morbidity and mortality. 50,53,77 In our previous modeling studies, Bruce and Bruce 9,10 compared the time courses of carboxymyoglobin (MbCO) and carboxyhemoglobin (HbCO) levels during and after CO exposures in a resting skeletal muscle compartment and in an ''other tissue'' compartment. These previous results 9, 10 demonstrated that the equilibration of CO between vascular and extravascular tissues during CO exposure, as well as the removal of extravascular CO during therapy, occurred over a much longer time scale than did the major changes in the vascular CO content as represented by %HbCO.…”
Section: Introductionmentioning
confidence: 99%
“…From studies in iron foundries and steel works associations have been reported between elevated blood pressure and exposure to heat or carbon monoxide (1 [8][9][10][11][12][13][14][15][16][17][18][19][20]. However, in a Norwegian study among workers in 1 of the FeSiISi-met plants, no difference in blood pressure between heat-and nonheat-exposed workers was revealed (21).…”
Section: Discussionmentioning
confidence: 99%